Air spring and application thereof
By using integrated porous materials in the air spring, the gas adsorption capacity is improved and the gas density in the closed cavity is adjusted, which solves the problem of excessive change in the air spring stiffness and achieves more flexible and stable air spring performance.
Patent Information
- Application Number
- CN202411672635.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-04
AI Technical Summary
The stiffness of the air spring changes too much during high-frequency vibration, resulting in limited handling and stability of the vehicle body. The greater the suspension movement, the stronger the air in the cavity is, the harder the spring, the greater the stiffer the stiffer it becomes, making it difficult to adjust.
Using mesh porous materials, through the structural design of micropores and large pores, the specific surface area of the material and the gas adsorption capacity are improved, and the density of gas in the closed cavity is adjusted, thereby adjusting the stiffness of the air spring.
通过吸附和脱附气体分子,缓和空气弹簧的压力变化,降低刚度变化,提高空气弹簧的柔性和稳定性,增强其在高频振动中的隔振消声能力。
Smart Images

Figure CN119554355A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of air springs, and in particular to an air spring and applications thereof. Background Art
[0002] An air spring is a vibration-damping and buffering device that is filled with compressed air in a sealed container and uses the compressibility of gas to achieve elastic action. It is widely used in self-adjusting air suspension machinery and equipment on commercial vehicles, buses, rail vehicles, machinery and equipment, and building bases.
[0003] Air springs are also called support rods, regulators, gas pressure rods, dampers, etc. The use of air springs in vehicles can not only optimize the riding comfort of vehicles, but also improve the maneuverability and stability of the fuselage. In addition, through the buffering and shock absorption effect, it reduces the contact, friction and wear between other components and extends the service life of components.
[0004] Air springs are commonly used elastic elements in air suspensions. They have good airtightness and compressibility. After compressed air is injected into the cavity, the pressure in the cavity is several or dozens of times higher than the atmospheric pressure. The compressibility of the gas is used to achieve a spring-like effect. In addition to air suspensions, air springs are also widely used in vibration isolation of many machines and equipment and building bases.
[0005] Compared with other types of springs, air springs are light in weight, have low internal friction, and have good vibration isolation and noise reduction capabilities in high-frequency vibrations. In addition, air springs can adjust the internal pressure by changing the amount of air to achieve ideal variable stiffness characteristics. When the load acting on the spring increases, the gas in the closed container is compressed, the air pressure increases, and the spring stiffness increases. Conversely, when the load decreases, the air pressure of the gas in the container decreases and the spring stiffness decreases accordingly. Therefore, when air springs are used on vehicle suspensions, the natural frequency of the vehicle body can remain basically unchanged even if the load is different. As the suspension deflects and the air is further compressed, the stiffness of the spring will rise sharply and become harder. For air springs, the greater the suspension travel, the more strongly the air in the cavity is compressed, the harder the spring is, the greater the stiffness, and the more difficult it is to control and stabilize the driving. Summary of the invention
[0006] In order to solve the above problems, an object of the present invention is to provide an air spring and application thereof.
[0007] In order to achieve the above-mentioned purpose, the present invention provides an air spring, which includes an outer shell, a connecting rod, a piston, and an embedded porous material; wherein the outer shell encloses a closed cavity, and the closed cavity is filled with gas; the piston is located in the closed cavity, one end of the connecting rod is connected to the piston, and the other end passes through the outer shell and is located outside the closed cavity; the closed cavity is divided into an independent closed cavity positive cavity and a closed cavity negative cavity by the piston, and the closed cavity positive cavity is the cavity where the connecting rod is located; the piston is provided with a through hole that can be opened and closed by itself, and the through hole is used to control the connection state between the closed cavity positive cavity and the closed cavity negative cavity; the embedded porous material is located in the closed cavity positive cavity, and the embedded porous material has micropores and macropores.
[0008] In the above-mentioned air spring, the piston fits tightly against the side wall of the closed cavity with no gap between them, so the positive cavity of the closed cavity and the negative cavity of the closed cavity can only be connected through the through hole in the piston. In some specific embodiments, the cross-sectional shape of the piston is the same as the cross-sectional shape of the closed cavity, and the radial dimension of the piston matches the radial dimension of the closed cavity to ensure that the piston is connected to the side wall of the closed cavity without gap. When the external load on the connecting rod changes, the piston can slide along the inner wall of the closed cavity.
[0009] In the above-mentioned air spring, the chimeric porous material filled in the positive cavity of the closed cavity has a high specific surface area and has a high adsorption and capture capacity for gas molecules such as air. The chimeric porous material can adsorb (pressurize) and desorb (depressurize) gas molecules according to the pressure changes in the environment in which it is located: when the environmental pressure increases, the chimeric porous material adsorbs gas molecules; when the environmental pressure decreases, the chimeric porous material desorbs gas molecules.
[0010] In the above-mentioned air spring, when the pressure of the positive cavity of the closed cavity increases, the chimeric porous material can quickly adsorb the gas molecules in the cavity; when the pressure of the positive cavity of the closed cavity decreases, the adsorbed gas molecules in the chimeric porous material are desorbed. With the help of the above-mentioned adsorption-desorption behavior of the chimeric porous material on the gas molecules, the density of the gas molecules in the closed cavity of the air spring can be changed, thereby changing the stiffness of the air spring; and the above-mentioned adsorption and desorption process can offset part of the pressure changes (pressurization and decompression) caused by compression and stretching, and alleviate the pressure changes of the air spring.
[0011] The chimeric porous material used in the present invention is a composite material composed of a carrier and a micro-mesoporous material, wherein the micro-mesoporous material has micropores and mesopores. The present invention is based on a carrier with macropores, and combines the carrier with a micro-mesoporous material to obtain a multi-level porous material with a macropore-mesoporous-micropore structure. Among them, the macropores and mesopores can provide a flow channel for the gas in the material, and the micropores can promote the adsorption and desorption of the gas by the material. By introducing the micro-mesoporous material, the chimeric porous material has a regular microporous structure, and the volume proportion of the micropores-mesoporous in the total pores in the material is increased, which can increase the specific surface area of the material, thereby increasing the adsorption capacity of gas molecules and making the air spring more flexible. Under the same compression force, the more flexible air spring has a shorter stroke range; or, under the same stroke, the more flexible air spring requires a lower compression force. In addition, the present invention can increase the mechanical properties of the carrier material by introducing microporous crystalline materials into the carrier, and the chimeric porous material obtained thereby has higher mechanical properties.
[0012] In some specific embodiments, the chimeric porous material further has mesopores. The mesopores in the chimeric porous material may come from the carrier and / or the micro-mesoporous material. In a specific embodiment, the mesopores in the chimeric porous material may mainly come from the carrier.
[0013] According to a specific embodiment of the present invention, in the mosaic porous material, the sum of the pore volumes of the micropores and mesopores is greater than or equal to 40% and less than or equal to 80% of the total pore volume of the mosaic porous material.
[0014] According to a specific embodiment of the present invention, in the mosaic porous material, the volume ratio of the micropores to the mesopores may be 2-5:1.
[0015] According to a specific embodiment of the present invention, the carrier has a pore structure, and the pore structure includes mesopores and macropores. The micro-mesoporous material has micropores and mesoporous structures. The pore structures of the carrier and the micro-mesoporous material can work synergistically to jointly improve the adsorption capacity of the chimeric porous material for gas molecules. In addition, the carrier itself has a molded appearance and a suitable size, and there is no need to introduce an adhesive to mold the chimeric porous material.
[0016] According to a specific embodiment of the present invention, the micro-mesoporous material and the carrier may be combined in such a way that the micro-mesoporous material is loaded on or embedded in the carrier. In some specific embodiments, the precursor solution of the micro-mesoporous material may be adsorbed by the carrier, and the precursor of the micro-mesoporous material may be converted into the micro-mesoporous material by reaction, drying, etc., thereby forming a multi-level porous material having a macroporous-mesoporous-microporous structure.
[0017] According to a specific embodiment of the present invention, the pore size of the mesopores of the micro-mesoporous material is 2nm-50nm, and the pore size of the macropores of the carrier is 50nm-100μm. The macropores and mesopores can provide channels for the circulation of gas molecules, and can also be used for the adsorption and desorption of gas molecules; the macropores can be used to load or grow micro-mesoporous materials, and the macropores can also be used together with the mesopores and micropores to adsorb and desorb gas molecules.
[0018] According to a specific embodiment of the present invention, the carrier may include one or a combination of two or more of a porous carbon material and porous silica.
[0019] In some specific embodiments, the porous carbon material may include one or a combination of two or more of soft carbon, hard carbon (such as lignite, etc.), carbon molecular sieve, activated carbon, and functionalized activated carbon (such as alkaline-modified activated carbon).
[0020] Among them, activated carbon is a black porous solid carbon, the main component of which is carbon, and contains a small amount of oxygen, hydrogen, sulfur, nitrogen, chlorine and other elements. The distribution of elements is irregular, and there are fine pores between the cross-connections. The pore size ranges from 1.5nm to 5μm. Activated carbon has the characteristics of low bulk density, rich pore structure, and large specific surface area. It is a commonly used industrial adsorption material; although the macroporous structure (pore size> 50nm) of activated carbon can provide a certain degree of adsorption sites during the gas adsorption process, the main function of the macroporous structure is to connect to the outside world and provide a diffusion channel. Therefore, introducing micro-mesoporous materials (such as zeolite molecular sieve grains, etc.) with nanometer or even micrometer-sized pores in the macroporous organizational structure can increase the overall gas adsorption capacity of the material without affecting gas diffusion.
[0021] In some specific embodiments, the activated carbon includes one or a combination of two or more of carbonized coconut shell (or coconut shell charcoal), tar charcoal, and coal charcoal.
[0022] In some specific embodiments, the carrier can withstand a temperature above 200° C. Thus, the carrier can withstand the crystallization temperature and crystallization process of micro-mesoporous materials such as molecular sieves, thereby preventing the structure of the carrier from being affected by the crystallization process.
[0023] According to a specific embodiment of the present invention, the micro-mesoporous material has two-dimensional channels and / or three-dimensional channels; further, the micro-mesoporous material may have two-dimensional microporous channels and / or three-dimensional microporous channels.
[0024] According to a specific embodiment of the present invention, the pore structure of the micro-mesoporous material is mainly micropores. The micro-mesoporous material has two-dimensional pores and / or three-dimensional pores. The pores are interconnected (i.e., the two-dimensional pores are interconnected, the three-dimensional pores are interconnected, and the two-dimensional pores and the three-dimensional pores are interconnected). and the pores are interconnected and can penetrate the porous material, so that gas molecules can freely enter and exit the pores of the micro-mesoporous material, which is conducive to the adsorption and desorption of gas molecules.
[0025] According to a specific embodiment of the present invention, the micro-mesoporous material includes an inorganic material having micro-mesoporosis and / or an organic framework material having micro-mesoporosis.
[0026] According to a specific embodiment of the present invention, the organic framework material with micro-mesoporosis includes covalent organic framework compounds (COFs) and / or metal organic framework materials (MOFs). The organic framework material with micro-mesoporosis has regularly arranged microporous channels inside, which can be used for adsorption and desorption of gas molecules.
[0027] According to a specific embodiment of the present invention, the inorganic material with micro-mesoporosis includes a molecular sieve; the molecular sieve generally has regular micropores, and by introducing the molecular sieve, the chimeric porous material can have regular intrinsic micropore channels. In a specific embodiment, mesopores can be introduced into the molecular sieve through experimental treatment to form a pore structure containing both micropores and mesopores. In addition, the structural skeleton elements of the molecular sieve are adjustable, so different heteroatoms can be introduced to modify the chemical and physical properties of the structure; the microscopic morphology of the zeolite molecular sieve is usually nano- or micron-sized particles, so it needs to be subsequently processed into blocks, columns, spheres and other morphological materials during the application process.
[0028] In some specific embodiments, the molecular sieve has pores with more than eight-membered rings (i.e., the molecular sieve has N-membered ring pores, N≥8). Specifically, the molecular sieve may have one or a combination of two or more of the following structures: STW, EWF, MEL, MEI, MOR, ITH, ITR, IMF, ITW, FER, MFI, MWW, RRO, JZO, JZT.
[0029] In some specific embodiments, the molecular sieve includes one or more combinations of phosphorus aluminum molecular sieve, pure silicon molecular sieve, silicon aluminum molecular sieve, silicon phosphorus aluminum molecular sieve. Among them, for silicon aluminum molecular sieve, in order to achieve structural electrical neutrality, an extra-framework cation is usually introduced into the silicon aluminum molecular sieve, and the silicon aluminum molecular sieve used in the present invention may further contain one or more combinations of hydrogen ions, monovalent metal ions, divalent metal ions, trivalent or higher metal ions, etc. More specifically, the molecular sieve may include one or more combinations of ZSM-5 molecular sieve, ZSM-11 molecular sieve, and A-type molecular sieve (LTA).
[0030] In some specific embodiments, the molecular sieve (such as pure silicon molecular sieve, silicon aluminum molecular sieve, silicon phosphorus aluminum molecular sieve, etc.) has a silicon aluminum atomic ratio (molar ratio of silicon aluminum atoms) greater than or equal to 20.
[0031] In some specific embodiments, the molecular sieve used in the present invention may have a higher specific surface area and a higher adsorption capacity for air. The specific surface area of the molecular sieve may be 250 m 2 / g or more, and can further reach 350m 2 / g or above.
[0032] In some specific embodiments, the micro-mesoporous material used in the present invention can be a crystalline material, such as a molecular sieve, and generally has a higher degree of crystallinity, so the micro-mesoporous material of the present invention has a higher degree of structural order and more regularly distributed pores than amorphous materials. Specifically, the molecular sieve has a degree of crystallinity of more than 80%.
[0033] In the present invention, the crystallinity is a relative crystallinity, which can be calculated based on the ratio of the total area of the crystallization peak to the total area of all the peaks (the sum of the areas of the crystallization peak and the amorphous peak), and the calculation formula is:
[0034] Crystallinity (%) = ∑A crystalline / (∑A crystalline +∑A amorphous ), where A crystalline is the area of the crystallization peak, A amorphous is the area of the amorphous peak.
[0035] According to a specific embodiment of the present invention, the mass of the micro-mesoporous material may account for more than 20% of the mass of the mosaic porous material. Further, the mass ratio of the carrier to the micro-mesoporous material is 4:1-1:4, such as 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4 and other specific values and ranges with any two of the above specific values as endpoints. Furthermore, the mass ratio of the carrier to the micro-mesoporous material can be controlled to be 2:1-1:2.
[0036] According to a specific embodiment of the present invention, the preparation method of the mosaic porous material may include:
[0037] The carrier is immersed in a solution of a micro-mesoporous material precursor and crystallized to obtain the chimeric porous material; wherein the preparation method of the chimeric porous material does not include a calcination step.
[0038] In the above-mentioned preparation method of the mosaic porous material, the particle size of the carrier as a raw material is generally controlled to be 30 meshes to 50 meshes, for example, 30 meshes to 40 meshes.
[0039] In the preparation method of the above-mentioned mosaic porous material, the carrier is a pretreated carrier, that is, the above-mentioned preparation method includes the operation of pretreating the carrier first and then immersing the pretreated carrier in the micro-mesoporous material precursor solution. The pretreatment process includes: treating the carrier at a high temperature of 450°C-800°C in a protective atmosphere for more than 2 hours.
[0040] The pretreatment process can adjust the specific process according to the different types of carriers. For example, when the carrier is activated carbon, the pretreatment process may include: subjecting the carrier to a high temperature treatment of 450°C-800°C in a protective atmosphere for more than 2 hours (such as 4 hours). The protective atmosphere may be nitrogen or the like. This pretreatment process will not have a significant effect on the distribution and orientation of the pores in the carrier, but can reduce the amount of water adsorbed by the carrier and fully carbonize the carrier. After the carrier is fully carbonized, the pores inside it are highly open and close to fully open, and the porosity and surface area of the carrier are also improved, which is beneficial to increase the carrier's loading capacity for porous materials. In some specific embodiments, the above-mentioned pretreatment may further include: before the high temperature treatment, subjecting the carrier to a first screening, ball milling, a second screening, and drying process.
[0041] In the above preparation method, when the carrier is porous silica, the pretreatment process of the carrier may include: mixing a silicon source (such as silica sol, etc.) with ammonia water to obtain a gel, drying to allow water molecules and ammonia molecules to escape, crushing, first screening, ball milling, second screening, drying, and completing the pretreatment.
[0042] In the above preparation method, when the carrier is hard carbon, the pretreatment process of the carrier may include: drying the hard carbon (lignite, etc.) to remove moisture and volatile components, carbonizing it at high temperature in a protective atmosphere (such as nitrogen), the carbonization temperature may be 1500°C, the carbonization time may be 12 hours, crushing the carbonized product, screening it for the first time, ball milling it, screening it for the second time, drying it, and completing the pretreatment.
[0043] In the above pretreatment process, the particle size of the carrier obtained after ball milling can reach 30-50 mesh, and the carrier after ball milling can remove irregular edges and corners and present an ellipsoidal or spherical shape. After the first screening, particles with a particle size of 20-40 mesh can be obtained, and after the second screening, particles with a particle size of 30-40 mesh can be obtained.
[0044] In the above-mentioned method for preparing the chimeric porous material, the solution of the micro-mesoporous material precursor includes a molecular sieve mother solution, such as a molecular sieve mother solution without a template.
[0045] In the preparation method of the above-mentioned chimeric porous material, the molecular sieve as the micro-mesoporous material is generally prepared by a synthesis method without a template agent, such as a seed induction method, etc. No template agent is introduced in the process of synthesizing the micro-mesoporous material, and the subsequent process of calcining to remove the template agent can be omitted, thereby retaining the pore structure in the micro-mesoporous material and the pore structure in the carrier. Therefore, the molecular sieve mother solution usually does not contain a template agent.
[0046] In the preparation method of the above-mentioned mosaic porous material, the molecular sieve mother liquor can be a solution that can prepare molecular sieves by crystallization. According to the type of elements contained in the molecular sieve, the molecular sieve mother liquor can include a combination of one or more of a silicon source, an aluminum source, and a phosphorus source. Further, the molecular sieve mother liquor can generally also include an alkali source, a mineralizer, etc., and the mineralizer is used to promote the dissolution of the silicon source and the aluminum source. The mineralizer can be a soluble inorganic salt, and the mineralizer can be removed in the washing process after crystallization. The ratio of each component in the molecular sieve mother liquor can adopt a conventional molecular sieve raw material ratio. For example, when the molecular sieve is a silicon-aluminum molecular sieve, the mass ratio of the aluminum source to the silicon source (in terms of SiO2) can be (1-5): 30, for example (1-3): 30.
[0047] In the preparation method of the above-mentioned mosaic porous material, the molecular sieve can be synthesized by seed induction method, and the molecular sieve mother solution can contain seed crystals. The amount of the seed crystals added can be added according to the conventional molecular sieve synthesis raw material ratio, for example, the mass ratio of seed crystals to silicon source can be (0.3-1.2):30.
[0048] In the preparation method of the above-mentioned chimeric porous material, the crystallization conditions can be adjusted according to the type and degree of crystallization of the micro-mesoporous material. For example, when the micro-mesoporous material is a molecular sieve, the crystallization conditions can be 120°C-160°C for 36h-96h. Generally, the crystallization temperature does not exceed 200°C (i.e., the crystallization temperature is less than or equal to 200°C) to avoid changes in the pore structure of the carrier during the crystallization process.
[0049] In the above-mentioned air spring, the height of the embedded porous material is generally controlled to be less than or equal to 30% of the height of the closed cavity.
[0050] In the above-mentioned air spring, the volume of the embedded porous material is generally controlled to be less than or equal to 30% of the volume of the closed cavity, and can be further controlled to be 10%-30% of the volume of the closed cavity.
[0051] By controlling the height and volume of the interlocking porous material, the interlocking porous material can be prevented from being crushed during the movement of the piston.
[0052] In some specific embodiments, the volume of gas adsorbed by the chimeric porous material can be more than twice the volume of the material itself. Compared with a single zeolite molecular sieve material, the chimeric porous material provided by the present invention, which is formed by a composite of a carrier and a micro-mesoporous material, has a macropore-mesoporous-micropore multi-level pore structure, which can utilize the characteristics of air molecules freely diffusing in macropores and mesopores, and utilize the small mesopores and micropore structures inside the material to enhance the specific surface area, thereby increasing the air adsorption capacity of the material and improving the flexibility of the air spring.
[0053] In the above-mentioned air spring, the embedded porous material is generally located at the bottom end of the positive cavity of the closed cavity (the end of the positive cavity of the closed cavity opposite to the piston and not passed through by the connecting rod). The position of the embedded porous material can be fixed by means of pasting or the like, or by packaging materials. In a specific embodiment, the packaging material can be a semi-rigid packaging material or a rigid packaging material. The semi-rigid packaging material can be made of organic fiber materials, such as rock wool, glass wool, carbon fiber and other inorganic fiber cotton, polyester fiber, or a combination of one or more thereof; the hard material can be made of metal materials, such as aluminum foil, copper foil, stainless steel mesh, aluminum mesh, copper mesh, or a combination of one or more thereof. In a specific embodiment, the mass of the packaging material is less than or equal to 10% of the mass of the embedded porous material.
[0054] In the above-mentioned air spring, the gas filled in the closed cavity may be compressed gas, and the pressure of the gas may be 1 bar-10 bar.
[0055] In some specific embodiments, the gas filled in the closed cavity includes one or a combination of two or more of air, nitrogen, CO2, carbon tetrafluoride, helium, neon, and argon.
[0056] In the above-mentioned air spring, the through hole in the piston includes a positive one-way hole and a negative one-way hole; a damping valve is respectively arranged in the positive one-way hole and the negative one-way hole, and the damping valve is used to control the opening and closing of the positive one-way hole and the negative one-way hole, and the positive one-way hole and the negative one-way hole are through holes that can be opened and closed by themselves. The damping valve arranged in the positive one-way hole can be called a positive one-way hole damping valve, and the damping valve arranged in the negative one-way hole can be called a negative one-way hole damping valve. When the positive one-way hole damping valve falls into the positive one-way hole, the positive one-way hole is closed; when the positive one-way hole damping valve leaves the positive one-way hole, the positive one-way hole is opened. When the negative one-way hole damping valve falls into the negative one-way hole, the negative one-way hole is closed; when the negative one-way hole damping valve leaves the negative one-way hole, the negative one-way hole is opened. When the positive one-way hole is opened, the gas flow direction is opposite to the gas flow direction when the negative one-way hole is opened.
[0057] In the above-mentioned air spring, the positive one-way hole and the negative one-way hole will neither open nor close at the same time, thereby maintaining the spring with a higher stiffness at a large stroke (large vibration amplitude) to prevent the shock absorber and the buffer block from being damaged.
[0058] Specifically, the working process of the positive one-way hole and the negative one-way hole in the air spring is: when the piston moves from the negative cavity of the closed chamber to the positive cavity of the sealed chamber, the positive one-way hole damping valve opens and the negative one-way hole damping valve closes; when the piston moves from the positive cavity of the closed chamber to the negative cavity of the closed chamber, the negative one-way hole damping valve opens and the positive one-way hole damping valve closes.
[0059] In the above air spring, the longitudinal sections of the positive one-way hole and the negative one-way hole may be respectively conical.
[0060] In the present invention, the end of the piston facing the negative cavity of the sealed chamber is recorded as the top end, and the end of the piston facing the positive cavity of the sealed chamber is recorded as the bottom end.
[0061] The longitudinal section of the positive one-way hole may be a cone, and the top aperture of the positive one-way hole is larger than the bottom aperture. Specifically, the ratio of the top aperture to the bottom aperture of the positive one-way hole damping valve may be greater than 1:1 and less than or equal to 10:1. The longitudinal section shape of the positive one-way hole damping valve is the same as the cross-sectional shape of the positive one-way hole, or may be a cone. The size of the positive one-way hole damping valve matches the size of the positive one-way hole. When the positive one-way hole damping valve completely falls into the positive one-way hole, the sides of the two are attached to each other without any gap. By adopting a conical structure, when the piston moves toward the positive cavity of the closed cavity, the gas in the positive cavity of the closed cavity will not flow into the negative cavity of the closed cavity in time (in a large amount in a short time), so as to maintain a variable pressure difference, thereby adjusting the stiffness of the air spring.
[0062] In the above air spring, the top opening area of the positive one-way hole accounts for less than 10% of the top surface area of the piston; the bottom opening area of the positive one-way hole can be less than 10% of the bottom surface area of the piston.
[0063] In the above air spring, the number of the positive one-way holes may be more than two.
[0064] In some specific embodiments, the cross-section of the negative one-way hole can be a positive cone, that is, the bottom aperture of the negative one-way hole is larger than the top aperture. Specifically, the ratio of the bottom aperture to the top aperture of the negative one-way hole damping valve can be greater than 1:1 and less than or equal to 10:1. The longitudinal cross-sectional shape of the negative one-way hole damping valve is the same as the cross-sectional shape of the negative one-way hole, or it can be an inverted cone. The size of the negative one-way hole damping valve matches the size of the negative one-way hole. When the negative one-way hole damping valve completely falls into the negative one-way hole, the two sides are attached to each other without gaps. By adopting a conical structure, when the piston moves toward the negative cavity of the closed cavity, the gas in the negative cavity of the closed cavity will not flow into the positive cavity of the closed cavity in time (in a short time and in large quantities), so as to maintain a variable pressure difference, thereby adjusting the stiffness of the air spring.
[0065] In the above air spring, the top opening area of the negative one-way hole accounts for less than 10% of the top surface area of the piston; the bottom opening area of the negative one-way hole can be less than 10% of the bottom surface area of the piston.
[0066] In the above air spring, the number of the negative one-way holes may be more than two.
[0067] In some specific embodiments, when there are more than two positive one-way holes and more than two negative one-way holes, the positive one-way holes and the negative one-way holes can be distributed alternately in the piston, with the positive one-way holes distributed symmetrically and the negative one-way holes distributed evenly.
[0068] In the above-mentioned air spring, a sealing ring for sealing may be provided at the junction of the connecting rod and the housing. In some specific embodiments, an outer sealing ring and an inner sealing ring may be provided at the outside (located outside the sealing cavity) and inside (located inside the sealing cavity) of the junction of the connecting rod and the housing, respectively, to ensure the sealing effect.
[0069] In the above-mentioned air spring, the height of the connecting rod is generally greater than the height of the closed cavity, that is, greater than the height of the shell.
[0070] According to a specific embodiment of the present invention, the working process of the above-mentioned air spring can be:
[0071] 1. When the air spring is in a compression condition (compressed by external force), the connecting rod moves from the negative cavity of the closed chamber to the positive cavity of the closed chamber, the positive one-way hole damping valve on the piston opens, and the negative one-way hole damping valve closes, the positive cavity of the closed chamber is connected with the negative cavity of the closed chamber, and the gas in the closed chamber flows from the positive cavity of the closed chamber to the negative cavity of the closed chamber;
[0072] Since the surface area of the piston is larger than the opening area of the positive one-way hole, the gas cannot enter the negative cavity of the closed cavity through the positive one-way hole in a short time, causing the pressure of the positive cavity of the closed cavity to be greater than the pressure of the negative cavity of the closed cavity, so that the connecting rod is subjected to damping force when moving toward the positive cavity of the closed cavity, and the stiffness increases; since the embedded porous material filled in the positive cavity of the closed cavity can absorb the gas molecules in the positive cavity of the closed cavity, the pressurization degree of the positive cavity of the closed cavity is reduced, the damping is reduced, and the stiffness is reduced, so that the air spring is buffered and moves softly when compressed;
[0073] 2. When the air spring is in the tension condition (stretched by external force), the connecting rod moves from the positive cavity of the closed chamber to the negative cavity of the closed chamber, the negative one-way hole damping valve on the piston opens, the positive one-way hole damping valve closes, the negative cavity of the closed chamber is connected with the positive cavity of the closed chamber, and the gas in the closed chamber flows from the negative cavity of the closed chamber to the positive cavity of the closed chamber;
[0074] Since the surface area of the piston is larger than the opening area of the negative one-way hole, the gas cannot enter the positive cavity of the closed chamber through the negative one-way hole in a short time. As a result, the pressure in the negative cavity of the closed chamber increases, and the connecting rod is subjected to damping force when it moves toward the negative cavity of the closed chamber, thereby increasing the stiffness. Since the volume of the positive cavity of the closed chamber increases and the pressure decreases, the gas molecules adsorbed by the mosaic porous material filled in the positive cavity of the closed chamber are decompressed and desorbed, thereby reducing the pressure difference between the negative cavity of the closed chamber and the positive cavity of the closed chamber, reducing the damping and stiffness, and allowing the air spring to be cushioned and move softly during rebound.
[0075] The air spring provided by the present invention can be used as an air shock absorber system or a shock absorbing device.
[0076] The present invention also provides a shock absorbing device, which includes the above-mentioned air spring provided by the present invention. In some specific embodiments, the shock absorbing device may include one or a combination of two or more of a bed frame gas pressure rod, a door and window cabinet gas pressure rod, a hood gas pressure rod, a cab gas pressure rod, a medical device gas pressure rod, an office chair gas pressure rod, a mountain bike front fork suspension and rear frame shock absorber, a car seat angle adjuster, and a car suspension shock absorber. The air spring of the present invention can adjust the size and dimensions of the closed cavity according to the type of shock absorbing device and the requirements of the application scenario.
[0077] The beneficial effects of the present invention include:
[0078] 1. Compared with conventional porous materials, the interlocking porous material used in the present invention has a higher specific surface area and can adsorb more gas; when the air spring filled with the interlocking porous material is compressed or stretched, it can improve the cushioning effect by adsorbing and desorbing more gas, reduce the stiffness of the spring, ease the pressure change, and improve stability.
[0079] 2. The present invention uses a mosaic porous material to adjust the ratio of the micro-mesoporous material to the carrier or adjust the type of the micro-mesoporous material, so as to achieve the control of the stroke specification of the air spring system. BRIEF DESCRIPTION OF THE DRAWINGS
[0080] Figure 1 Schematic diagram of the structure of the air spring of Examples 1 to 3.
[0081] Figure 2 This is the BET test result of the activated carbon material of Preparation Example 1.
[0082] Figure 3 This is the pore size distribution diagram of the activated carbon material of Preparation Example 1.
[0083] Figure 4 This is a scanning electron microscope image of the activated carbon material of Preparation Example 1.
[0084] Figure 5 This is the macropore data test result of the activated carbon material of Preparation Example 1.
[0085] Figure 6 This is the BET test result of the mosaic porous material of Example 1.
[0086] Figure 7 This is the mesopore size distribution diagram of the mosaic porous material of Example 1.
[0087] Figure 8 This is a diagram of the micropore size distribution of the mosaic porous material of Example 1.
[0088] Fig. 9 This is a scanning electron microscope image of the mosaic porous material of Example 1.
[0089] Fig.10 This is the macropore size distribution diagram of the mosaic porous material of Example 1.
[0090] Fig.11 This is a microscopic scanning electron microscope image of the ZSM-11 molecular sieve of Comparative Example 3.
[0091] Fig.12 This is the BET test result of the ZSM-11 molecular sieve of Comparative Example 3.
[0092] Fig.13 This is the pore size distribution diagram of the ZSM-11 molecular sieve of Comparative Example 3.
[0093] Fig.14 The compression damping force-stroke diagram of the air springs of Examples 1 to 3 and Comparative Examples 1 to 4.
[0094] Fig.15The tensile damping force-stroke diagram of the air springs of Examples 1 to 3 and Comparative Examples 1 to 4.
[0095] Explanation of symbols
[0096] Connecting rod 1, outer sealing ring 2, cavity outer surface 3, inner sealing ring 4, cavity inner surface 5, closed cavity negative cavity 6, positive one-way hole damping valve 7, piston 8, positive one-way hole 9, negative one-way hole 10, negative one-way hole damping valve 11, closed cavity positive cavity 12, embedded porous material 13, closed cavity positive cavity bottom end 121, packaging material 14. DETAILED DESCRIPTION
[0097] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0098] Preparation Example 1
[0099] This preparation example provides a porous material, and the preparation method thereof includes:
[0100] The commercially available activated carbon was sieved to obtain activated carbon particles of 30 to 40 meshes, and then the sieved activated carbon was placed in a 120° C. forced air oven to dry for 12 hours; the dried activated carbon particles were placed in a room temperature dryer for later use.
[0101] Preparation Example 2
[0102] This preparation example provides a porous material, and the preparation method thereof includes:
[0103] Weigh 100.0 g of the activated carbon in Preparation Example 1 and load it into a fiber mesh cloth (the mesh size of the fiber mesh cloth is higher than the particle size of the activated carbon particles) that has been hot-pressed into a fixed geometric shape. Then, the fiber mesh cloth is sealed to form an activated carbon material block with the fiber mesh cloth as the packaging material.
[0104] Preparation Example 3
[0105] This preparation example provides a porous material, and the preparation method thereof includes:
[0106] 1. Weigh 1000.0 g of silica sol (SiO2 content 30 wt%) as a silicon source, add 30.0 g of NaOH as an alkali source and mineralizer, and stir rapidly at room temperature for 0.5 h, which is recorded as solution A;
[0107] 2. Weigh 26.260 g Al(NO3)3·9H2O as aluminum source, dissolve it in 910.0 g deionized water, and stir rapidly at room temperature for 0.5 h, which is recorded as solution B;
[0108] 3. Slowly add solution B to solution A, and stir continuously at room temperature for 0.5 h to obtain a mixed solution; add 5.0 g of ZSM-11 molecular sieve seed crystals to the mixed solution, and stir at room temperature for 0.5 h to complete the preparation of the molecular sieve mother solution;
[0109] 4. The mixture was transferred to a PTFE-lined reactor and crystallized at a constant temperature of 140° C. for 48 h. After the crystallization, the molecular sieve mother was liquid-crystallized to form a ZSM-11 molecular sieve. The crystallized product was centrifuged and washed several times and dried at 100° C. overnight to obtain a ZSM-11 zeolite molecular sieve material (after elemental analysis, the silicon-aluminum atomic ratio of the ZSM-11 zeolite molecular sieve material was about 70).
[0110] 5. Then, 100 g of ZSM-11 zeolite molecular sieve material was weighed and filled into a fiber mesh cloth that was hot-pressed into a fixed geometric shape, and then the fiber mesh cloth was sealed to form a zeolite molecular sieve material block with a polypropylene fiber mesh cloth as a packaging material. In order to prevent the zeolite molecular sieve material block from falling powder, 8.0 g of a 40% acrylic acid (here, polyacrylate) solution was sprayed on the surface of the zeolite molecular sieve material block, and ultraviolet light was irradiated at the same time to accelerate the curing of the polyacrylate, and then dried in a 60° C. blast oven for 6 hours for standby use.
[0111] Preparation Example 4
[0112] This preparation example provides a porous material, and the preparation method thereof includes:
[0113] Weigh 1000.0 g of silica sol (SiO2 content 30 wt%) as a silicon source, add 30.0 g of NaOH as an alkali source and mineralizer, and stir rapidly at room temperature for 0.5 h, which is recorded as solution A;
[0114] 2. Weigh 26.260 g Al(NO3)3·9H2O as aluminum source, dissolve it in 910.0 g deionized water, and stir rapidly at room temperature for 0.5 h, which is recorded as solution B;
[0115] 3. Slowly add solution B to solution A, and stir continuously at room temperature for 0.5 h to obtain a mixed solution; add 5.0 g of ZSM-5 molecular sieve seed crystals to the mixed solution, and stir at room temperature for 0.5 h to complete the preparation of the molecular sieve mother solution;
[0116] 4. The mixture was transferred to a PTFE-lined reactor and crystallized at a constant temperature of 120° C. for 48 h. After the crystallization, the molecular sieve mother was liquid-crystallized to form a ZSM-5 molecular sieve. The crystallized product was centrifuged and washed several times and dried at 100° C. overnight to obtain a ZSM-5 zeolite molecular sieve material (after elemental analysis, the silicon-aluminum atomic ratio of the ZSM-5 zeolite molecular sieve material was about 71).
[0117] 5. Then weigh 100g of ZSM-5 zeolite molecular sieve material and fill it into a fiber mesh cloth that has been hot-pressed into a fixed geometric shape. Then seal the fiber mesh cloth to form a zeolite molecular sieve material block with a polypropylene fiber mesh cloth as a packaging material. In order to prevent the zeolite molecular sieve material block from falling off, spray 8.0g of 40% acrylic acid (polyacrylate is used here) solution on the surface of the zeolite molecular sieve material block, and irradiate it with ultraviolet light at the same time to accelerate the curing of the polyacrylate. Then dry it in a 60°C forced air oven for 6h for use.
[0118] Example 1
[0119] This embodiment provides an air spring, such as Figure 1 As shown, the air spring includes a housing, a connecting rod 1 , a piston 8 , and an embedded porous material 13 .
[0120] The shell forms a closed cavity, and the closed cavity is filled with gas. The pressure of the gas generally does not exceed 10 bar; the type of gas can be one of air, nitrogen, CO2, carbon tetrafluoride, helium, neon, argon, or a combination of two or more. In this embodiment, the inner diameter of the closed cavity is 40 mm and the height is 100 mm.
[0121] The piston 8 is located in the closed cavity and fits tightly with the inner wall of the closed cavity, dividing the closed cavity into a mutually independent closed cavity positive cavity 12 and a closed cavity negative cavity 6. The piston 8 can slide along the inner wall of the closed cavity, thereby changing the volume of the closed cavity positive cavity 12 and the closed cavity negative cavity 6. The closed cavity positive cavity 12 and the closed cavity negative cavity 6 are both filled with gas. When the air spring is in the initial state, the air pressure of the closed cavity positive cavity 12 and the closed cavity negative cavity 6 is the same. In this embodiment, the piston 8 is a stainless steel piston.
[0122] The piston 8 is provided with a positive one-way hole 9 and a negative one-way hole 10 , which can respectively control the communication between the positive cavity 12 of the sealed cavity and the negative cavity 6 of the sealed cavity.
[0123] The longitudinal section of the positive one-way hole 9 is conical, and the ratio of the top diameter to the bottom diameter of the positive one-way hole 9 is greater than 1:1 and less than or equal to 10:1; the top opening area of the positive one-way hole 9 is less than or equal to 10% of the top surface area of the piston 8, and the bottom opening area of the positive one-way hole 9 is less than or equal to 10% of the bottom surface area of the piston 8 (the top and bottom directions are in the order of Figure 1 As an example). In this embodiment, the top diameter of the positive one-way hole 9 is 0.50 mm, and the bottom diameter is 0.1 mm.
[0124] A positive one-way hole damping valve 7 is provided in each positive one-way hole 9, and the shape of the positive one-way hole damping valve 7 is the same as that of the positive one-way hole 9, and the size of the positive one-way hole damping valve 7 matches the size of the positive one-way hole 9. The positive one-way hole damping valve 7 can control the opening and closing of the positive one-way hole 9. When the positive one-way hole damping valve 7 falls into the positive one-way hole 9, the two are attached to each other without a gap, and the positive one-way hole 9 is closed; when the two are separated, the positive one-way hole 9 is opened.
[0125] The longitudinal section of the negative one-way hole 10 is conical, and the ratio of the bottom diameter to the top diameter of the negative one-way hole 10 is greater than 1:1 and less than or equal to 10:1; the top opening area of the negative one-way hole 10 is less than or equal to 10% of the top surface area of the piston 8, and the bottom opening area of the negative one-way hole 10 is less than or equal to 10% of the bottom surface area of the piston 8. In this embodiment, the bottom diameter of the negative one-way hole 10 is 0.5 mm, and the top diameter is 0.1 mm.
[0126] A negative one-way hole damping valve 11 is provided in each negative one-way hole 10, and the shape of the negative one-way hole damping valve 11 is the same as that of the negative one-way hole 10, and the size of the negative one-way hole damping valve 11 matches the size of the negative one-way hole 10. The negative one-way hole damping valve 11 can control the opening and closing of the negative one-way hole 10. When the negative one-way hole damping valve 11 falls into the negative one-way hole 10, the two are attached to each other without a gap, and the negative one-way hole 10 is closed; when the two are separated, the negative one-way hole 10 is opened.
[0127] In this embodiment, there are more than two positive one-way holes 9 and negative one-way holes 10. The positive one-way holes 9 and negative one-way holes 10 are alternately distributed in the piston 8, and the positive one-way holes 9 are evenly and symmetrically distributed, and the negative one-way holes 10 are evenly and symmetrically distributed.
[0128] One end of the connecting rod 1 is connected to the piston 8, and the other end passes through the shell and extends out of the closed cavity. The connecting rod 1 is used to control the movement of the piston 8 in the closed cavity. The length of the connecting rod 1 is greater than the outer height of the closed cavity (i.e., the height of the shell).
[0129] An outer sealing ring 2 is provided at the connection between the connecting rod 1 and the outer shell in the outer surface 3 of the cavity, and an inner sealing ring 4 is provided inside the connection between the connecting rod 1 and the outer shell in the inner surface 5 of the cavity (inside the closed cavity). The outer sealing ring 2 and the inner sealing ring 4 can ensure the airtightness of the connection between the connecting rod 1 and the outer shell, thereby ensuring the airtightness of the closed cavity.
[0130] The embedded porous material 13 is located in the closed cavity 12 and is generally fixed to the bottom of the closed cavity 12. The height of the embedded porous material 13 is less than or equal to 30% of the height of the closed cavity, and the volume of the embedded porous material 13 is 10%-30% of the volume of the closed cavity. In this embodiment, the height of the embedded porous material 13 is 15 mm.
[0131] The embedded porous material 13 can be directly fixed to the bottom end of the closed cavity 12 by bonding or the like, or fixed to the bottom end 121 of the closed cavity by the packaging material 14. In this embodiment, the embedded porous material 13 is fixed to the center of the bottom end 121 of the closed cavity by the packaging material 14. In this embodiment, the packaging material is a fiber mesh with a pore size of 120 meshes.
[0132] In actual use of some embodiments, the gas filled in the closed cavity is compressed air with a pressure of 5 bar, and the amplitude frequency of the air spring is 2 Hz. That is, the piston of the air spring completes the compression-rebound process twice within 1 second.
[0133] The preparation method of the mosaic porous material in this embodiment includes:
[0134] 1. Weigh 1000.0 g of silica sol (SiO2 content 30 wt%) as a silicon source, add 30.0 g of NaOH as an alkali source and mineralizer, and stir rapidly at room temperature for 0.5 h, which is recorded as solution A;
[0135] 2. Weigh 26.260 g Al(NO3)3·9H2O as aluminum source, dissolve it in 910.0 g deionized water, and stir rapidly at room temperature for 0.5 h, which is recorded as solution B;
[0136] 3. Slowly add solution B to solution A, and stir continuously at room temperature for 0.5 h to obtain a mixed solution; add 5.0 g of ZSM-11 molecular sieve seed crystals to the mixed solution, and stir at room temperature for 0.5 h to complete the preparation of the molecular sieve mother solution;
[0137] 4. 150.0 g of the activated carbon granules prepared in Preparation Example 1 were added to the above molecular sieve mother liquor, and the mixture was stirred for 1 h to obtain a mixture, which was transferred to a PTFE-lined reactor and crystallized at 140° C. for 48 h. After the crystallization, the molecular sieve mother liquid crystallized to form a ZSM-11 molecular sieve, and the crystallized product was centrifuged and washed several times, and dried at 100° C. overnight to obtain a chimeric porous material. The mass of the molecular sieve accounted for 58.5% of the mass of the chimeric porous material.
[0138] 5. The obtained interlocking porous material is subjected to simple oscillation screening. The zeolite molecular sieve material that is not completely loaded inside or on the surface of the activated carbon particles can be removed during the oscillation screening process, and the interlocking porous material with a particle size of 35-40 mesh is screened out; then 100.0g of the interlocking porous material is weighed and loaded into a fiber mesh cloth that is hot-pressed into a fixed geometric shape, and then the fiber mesh cloth is sealed to form an interlocking porous material block with the fiber mesh cloth as the packaging material, wherein the mass of the fiber mesh cloth is 4.5g.
[0139] Example 2
[0140] This embodiment provides an air spring, the structure of which is similar to that of Embodiment 1, except that different embedded porous materials are used.
[0141] The preparation method of the mosaic porous material of this embodiment includes:
[0142] 1. Weigh 1000.0 g of silica sol (SiO2 content 30 wt%) as a silicon source, add 30.0 g of NaOH as an alkali source and mineralizer, and stir rapidly at room temperature for 0.5 h, which is recorded as solution A;
[0143] 2. Weigh 26.260 g Al(NO3)3·9H2O as aluminum source, dissolve it in 910.0 g deionized water, and stir rapidly at room temperature for 0.5 h, which is recorded as solution B;
[0144] 3. Slowly add solution B to solution A, and stir continuously at room temperature for 0.5 h to obtain a mixed solution; add 5.0 g of ZSM-5 molecular sieve seed crystals to the mixed solution, and stir at room temperature for 0.5 h to complete the preparation of the molecular sieve mother solution;
[0145] 4. 150.0 g of the activated carbon granules prepared in Preparation Example 1 were added to the above molecular sieve mother liquor, and the mixture was stirred for 1 h to obtain a mixture, which was transferred to a PTFE-lined reactor and crystallized at 120° C. for 48 h. After the crystallization, the molecular sieve mother liquid crystallized to form a ZSM-5 molecular sieve, and the crystallized product was centrifuged and washed several times, and dried at 100° C. overnight to obtain a chimeric porous material. The mass of the molecular sieve accounted for 60.2% of the mass of the chimeric porous material.
[0146] 5. The obtained interlocking porous material is subjected to simple oscillation screening. The zeolite molecular sieve material that is not completely loaded inside or on the surface of the activated carbon particles can be removed during the oscillation screening process, and the interlocking porous material with a particle size of 35-40 mesh is screened out; then 100.0g of the interlocking porous material is weighed and loaded into a fiber mesh cloth that is hot-pressed into a fixed geometric shape, and then the fiber mesh cloth is sealed to form an interlocking porous material block with the fiber mesh cloth as the packaging material, wherein the mass of the fiber mesh cloth is 4.5g.
[0147] Example 3
[0148] This embodiment provides an air spring, the structure of which is similar to that of Embodiment 1, except that different embedded porous materials are used.
[0149] The preparation method of the mosaic porous material of this embodiment includes:
[0150] 1. Weigh 700.0 g of silica sol (SiO2 content 30 wt%) as a silicon source, add 46.6 g of NaOH as an alkali source and mineralizer, and stir rapidly at room temperature for 0.5 h, which is recorded as solution A;
[0151] 2. Weigh 29.29 g Al(NO3)3·9H2O as aluminum source, dissolve it in 210.0 g deionized water, and stir rapidly at room temperature for 0.5 h, which is called solution B.
[0152] 3. Slowly add solution B to solution A, and continue stirring at room temperature for 0.5 h to obtain a mixed solution. Add 4.0 g of type A molecular sieve seed crystals to the mixed solution to complete the preparation of the molecular sieve mother solution;
[0153] 4. Add 150.0 g of the activated carbon granules prepared in Preparation Example 1 to the above molecular sieve mother liquor, continue stirring for 1 hour to obtain a mixture, transfer the mixture to a PTFE-lined reactor, and crystallize at 100° C. for 24 hours; after the crystallization, the molecular sieve mother liquid crystallizes to form a type A molecular sieve (LTA, silicon-aluminum atomic ratio of 41) with 8R channels, centrifuge and wash the crystallized product several times, and dry at 100° C. overnight to obtain a chimeric porous material. The mass of the molecular sieve accounts for 60.4% of the mass of the chimeric porous material.
[0154] 5. The obtained interlocking porous material is subjected to simple oscillation screening. The zeolite molecular sieve material that is not completely loaded inside or on the surface of the activated carbon particles can be removed during the oscillation screening process, and the interlocking porous material with a particle size of 35-40 mesh is screened out; then 100.0g of the interlocking porous material is weighed and loaded into a fiber mesh cloth that is hot-pressed into a fixed geometric shape, and then the fiber mesh cloth is sealed to form an interlocking porous material block with the fiber mesh cloth as the packaging material, wherein the mass of the fiber mesh cloth is 4.5g.
[0155] The working process of the air springs of Embodiment 1, Embodiment 2 and Embodiment 3 is as follows:
[0156] 1. When the air spring is in a compression condition (such as applying an external load to compress the air spring), the connecting rod 1 drives the piston 8 to move toward the positive cavity 12 of the closed cavity, the negative one-way hole 10 on the piston 8 is closed (the negative one-way hole damping valve and the negative one-way hole 10 are close to each other without a gap), and the positive one-way hole 9 is opened (the positive one-way hole damping valve and the positive one-way hole 9 are separated, and there is a gap between them), and the gas in the positive cavity 12 of the closed cavity flows unidirectionally toward the negative cavity 6 of the closed cavity;
[0157] During the continuous movement of the piston 8, since the surface area of the piston 8 is larger than the opening area of the positive one-way hole 9, the gas in the positive cavity 12 of the closed cavity cannot pass through the positive one-way hole 9 in a short time, and the volume of the positive cavity 12 of the closed cavity continues to decrease, resulting in an increase in the pressure of the positive cavity 12 of the closed cavity, which is greater than the pressure of the negative cavity 6 of the closed cavity. The pressure difference between the two cavities causes the piston 8 to be subjected to a damping force during its movement toward the positive cavity 12 of the closed cavity, and the stiffness increases; at the same time, as the pressure of the positive cavity 12 of the closed cavity increases, the embedded porous material 13 in the positive cavity 12 of the closed cavity can absorb the gas in the positive cavity 12 of the closed cavity (the embedded porous material 13 can absorb gas molecules larger than twice its own volume), reduce the pressure difference between the two cavities, reduce the damping force and stiffness, and make the air spring buffered and move softly during compression;
[0158] 2. When the air spring is in a tensioning condition (e.g., the external load of the compressed air spring is reduced, causing the air spring to rebound from the compression limit), the piston 8 moves toward the negative cavity 6 of the closed cavity, the positive one-way hole 9 on the piston 8 is closed (the positive one-way hole damping valve and the positive one-way hole 9 are close to each other with a gap), and the negative one-way hole 10 is opened (the negative one-way hole damping valve and the negative one-way hole 10 are separated, and there is a gap between the two), and the gas in the negative cavity 6 of the closed cavity flows unidirectionally toward the positive cavity 12 of the closed cavity;
[0159] During the continuous movement of the piston 8, since the surface area of the piston 8 is larger than the opening area of the negative one-way hole 10, the gas in the negative chamber 6 of the closed chamber cannot pass through the negative one-way hole 10 in a short time. As the volume of the negative chamber 6 of the closed chamber decreases and the pressure in the negative chamber 6 increases, the piston 8 is subjected to a damping force during the movement toward the negative chamber 6 of the closed chamber, and the stiffness increases; at the same time, as the volume of the positive chamber 12 of the closed chamber increases, the mosaic porous material 13 in the positive chamber 12 of the closed chamber can decompress the gas in the positive chamber 12 of the closed chamber adsorbed in the desorption step 1, alleviate the pressure difference between the positive chamber 12 of the closed chamber and the negative chamber 6 of the closed chamber, reduce the damping force and stiffness, and make the air spring buffered and move softly during rebound.
[0160] Comparative Example 1
[0161] This comparative example provides an air spring, the structure of which is similar to that of Example 1, except that different embedded porous materials are used.
[0162] In this comparative example, an activated carbon material block with a fiber mesh as a packaging material of equal mass in Preparation Example 2 is used to replace the mosaic porous material block with a fiber mesh as a packaging material in Example 1.
[0163] Comparative Example 2
[0164] This comparative example provides an air spring, the structure of which is similar to that of Example 1, except that different embedded porous materials are used.
[0165] In this comparative example, the mosaic porous material of Example 1 is replaced by the zeolite molecular sieve material block of Preparation Example 3 with an equal mass.
[0166] Comparative Example 3
[0167] This comparative example provides an air spring, the structure of which is similar to that of Example 1, except that different embedded porous materials are used.
[0168] In this comparative example, the molecular sieve material block of Preparation Example 4 with the same mass is used to replace the mosaic porous material of Example 1.
[0169] Comparative Example 4
[0170] This comparative example provides an air spring, the structure of which is similar to that of Example 1, except that this comparative example does not provide an embedded porous material in the closed cavity, and only fills the closed cavity with gas.
[0171] Characterization and testing of samples from the above experiments:
[0172] Figure 2 , Figure 3 , Figure 4 , Figure 5 The BET test results, pore size distribution diagram, microscopic scanning electron microscope diagram and macropore data test results of the activated carbon material of Preparation Example 1 are shown respectively. Figure 2 The test results show that the overall specific surface area of the activated carbon material of Preparation Example 1 is 1865m 2 / g, pore volume is 0.8954cm 3 / g; Figure 3 The pore size distribution diagram shows that the most probable pore size of micropores is 1.72nm, and the most probable pore size of mesopores is 30.59nm. Figure 4 It can be seen that the activated carbon material has an open macroporous channel structure. Figure 5 It can be obtained that the most probable macropore diameters of the activated carbon material in Preparation Example 1 are 1.6 μm and 6.9 μm.
[0173] Figure 6 , Figure 7 , Figure 8 , Fig. 9 , Fig.10 They are respectively the BET test results, mesopore pore size distribution diagram, micropore pore size distribution diagram, microscopic scanning electron microscope diagram, and macropore pore size distribution diagram of the chimeric porous material of Example 1. Figures 5 to 8 It can be seen that the overall specific surface area of the mosaic porous material is 2277m 2 / g, pore volume is 1.1558cm 3 / g; the pore size distribution diagram shows that the most probable pore sizes of micropores are 0.55nm and 1.72nm, and the most probable pore size of mesopores is 18.39nm; after testing, the most probable pore sizes of macropores are 1.2μm, 6.0μm and 6.8μm. Compared with the porous material of Preparation Example 1, the chimeric porous material of Example 1 reduces the size and proportion of mesopores by introducing zeolite molecular sieve crystals, but the reduction in mesopore size can effectively increase the specific surface area of the material, and the increase in specific surface area can further enhance the gas adsorption capacity of the chimeric porous material. Fig. 9 It can be seen that the molecular sieve particles are embedded in the pores of the activated carbon carrier. According to calculations, in the mosaic porous material of Example 1, the sum of the pore volume of micropores and mesopores is 68.7% of the total pore volume, and the ratio of the pore volume of micropores to mesopores is 5:1; in Example 2, the sum of the pore volume of micropores and mesopores is 75.4% of the total pore volume, and the ratio of the pore volume of micropores to mesopores is 4:1; in Example 3, the sum of the pore volume of micropores and mesopores is 79.9% of the total pore volume, and the ratio of the pore volume of micropores to mesopores is 2:1.
[0174] Fig.11 , Fig.12 , Fig.13 The microscopic scanning electron microscope image, BET test results, and pore size distribution diagram of the ZSM-11 molecular sieve in Comparative Example 3. The ZSM-11 grain size is about 0.7 μm, and the specific surface area of ZSM-11 is 363 m 2 / g, and the total pore volume is 0.2502cm 3 / g, the most probable pore size of micropores is 0.53nm, and the most probable pore size of mesopores is 2.25nm.
[0175] Fig.14 The compression damping force-stroke diagram of the air springs of Examples 1 to 3 and Comparative Examples 1 to 4.
[0176] No porous material is added to the air spring of Comparative Example 4. Taking the results of Comparative Example 4 as a comparison basis, it can be seen that the compression damping force of the air springs to which activated carbon blocks (Comparative Example 1), molecular sieve blocks (Comparative Example 2 and Comparative Example 3), and mosaic porous materials (Example 1, Example 2, and Example 3) are added is reduced at the same stroke. This shows that adding porous material blocks to the air spring can make the compression process of the air spring smoother.
[0177] Comparing the test results of Comparative Examples 1-3 with those of Examples 1-3, it can be seen that the damping force of the air spring is most significantly reduced after adding the intercalated porous material, followed by the air spring with the molecular sieve block, and the damping force of the air spring with the porous activated carbon material is the smallest. Under the same stroke, the compression damping force of the air springs of Comparative Examples 2 and 3 is close, and the compression damping force of the air springs of Examples 1 and 2 is close, because the ZSM-11 molecular sieve and the ZSM-5 molecular sieve have very similar structures and properties, and therefore exhibit similar compression damping forces.
[0178] Fig.15 The tensile damping force-stroke diagram of the air springs of Examples 1 to 3 and Comparative Examples 1 to 4.
[0179] No porous material is added to the air spring of Comparative Example 4. Taking the results of Comparative Example 4 as a comparison basis, it can be seen that the tensile damping force of the air springs to which activated carbon blocks (Comparative Example 1), molecular sieve blocks (Comparative Example 2 and Comparative Example 3), and mosaic porous materials (Example 1, Example 2, and Example 3) are added is reduced at the same stroke. This shows that adding porous material blocks to the air spring can make the stretching process of the air spring smoother.
[0180] Comparing the test results of Comparative Examples 1-3 with those of Examples 1-3, it can be seen that the damping force of the air spring is most significantly reduced after adding the intercalated porous material, followed by the air spring with the molecular sieve block, and the damping force of the air spring with the porous activated carbon material is the smallest. Under the same stroke, the tensile damping force of the air springs of Comparative Examples 2 and 3 is close, and the tensile damping force of the air springs of Examples 1 and 2 is close, because the ZSM-11 molecular sieve and the ZSM-5 molecular sieve have very similar structures and properties, and therefore exhibit similar tensile damping forces.
[0181] Combined with the test results of Examples 1 to 3, it can be seen that the present invention can adjust the stroke specifications of the air spring system by adjusting the type of zeolite molecular sieve material.
[0182] It can be seen from the above test results that the present invention can reduce the damping force of the air spring under compression or tension conditions and make the damping force change slowly by adding a specific embedded porous material into the air spring.
Claims
1. An air spring comprising a housing, a connecting rod, a piston, and a mosaic porous material; in, The shell forms a closed cavity, and the closed cavity is filled with gas; The piston is located in the closed cavity, one end of the connecting rod is connected to the piston, and the other end passes through the shell and is located outside the closed cavity; The sealed cavity is divided into an independent sealed positive cavity and a sealed negative cavity by a piston, and the sealed positive cavity is the cavity where the connecting rod is located; the piston is provided with a through hole that can be opened and closed automatically, and the through hole is used to control the connection state between the sealed positive cavity and the sealed negative cavity; The embedded porous material is located in the positive cavity of the closed cavity, and the embedded porous material has micropores and macropores.
2. The air spring according to claim 1, wherein: The chimeric porous material has mesopores; Preferably, in the mosaic porous material, the sum of the pore volumes of the micropores and mesopores is greater than or equal to 40% and less than or equal to 80% of the total pore volume, and the pore volume ratio of the micropores to the mesopores is (2-5):
1.
3. The air spring according to claim 2, wherein: The embedded porous material is composed of a carrier and a micro-mesoporous material, the carrier has a pore structure including mesopores and macropores, and the micro-mesoporous material is loaded on or embedded in the carrier; Preferably, the pore size of the mesopores of the micro-mesoporous material is 2nm-50nm, and the pore size of the macropores of the carrier is 50nm-100μm; Preferably, the micro-mesoporous material has two-dimensional channels and / or three-dimensional channels, and the pore size of the two-dimensional channels and / or three-dimensional channels in the micro-mesoporous material is The pores are interconnected.
4. The air spring according to claim 3, wherein: The carrier comprises one or a combination of two or more of a porous carbon material and a porous silica; Preferably, the porous carbon material comprises one or a combination of two or more of soft carbon, hard carbon, carbon molecular sieve, activated carbon, and functionalized activated carbon; More preferably, the activated carbon comprises one or a combination of two or more of carbonized coconut shell, tar charcoal, and coal charcoal; Preferably, the carrier can withstand temperatures above 200°C.
5. The air spring according to claim 3, wherein: The micro-mesoporous material includes an inorganic material having micro-mesoporosis and / or an organic framework material having micro-mesoporosis; Preferably, the organic framework material having micro-mesoporosis comprises a covalent organic framework compound and / or a metal organic framework material.
6. The air spring according to claim 5, wherein: The inorganic material having micro-mesoporosis includes molecular sieve; Preferably, the molecular sieve has pores with more than eight-membered rings, and the molecular sieve preferably has one or a combination of two or more of the following structures: STW, EWF, MEL, MEI, MOR, ITH, ITR, IMF, ITW, FER, MFI, MWW, RRO, JZO, JZT; Preferably, the crystallinity of the molecular sieve is above 80%; Preferably, the specific surface area of the molecular sieve is 250 m 2 / g or more, more preferably 350m 2 / g or more; Preferably, the molecular sieve comprises one or a combination of two or more of phosphorus aluminum molecular sieve, pure silicon molecular sieve, silicon aluminum molecular sieve, and silicon phosphorus aluminum molecular sieve; More preferably, the molecular sieve comprises one or a combination of two or more of ZSM-5 molecular sieve, ZSM-11 molecular sieve and type A molecular sieve; More preferably, the silicon to aluminum atomic ratio of the molecular sieve is greater than or equal to 20.
7. The air spring according to claim 3, wherein: The mass of the micro-mesoporous material accounts for more than 20% of the mass of the mosaic porous material; More preferably, the mass ratio of the carrier to the micro-mesoporous material is 4:1-1:4; Further preferably, the mass ratio of the carrier to the micro-mesoporous material is 2:1-1:
2.
8. The air spring according to claim 1, wherein: The preparation method of the chimeric porous material comprises: immersing a carrier in a solution of a micro-mesoporous material precursor, crystallizing, and obtaining the chimeric porous material; wherein the preparation method of the chimeric porous material does not include a calcination step; Preferably, the carrier is a pretreated carrier, and the pretreatment process includes: treating the carrier at a high temperature of 450° C.-800° C. for more than 2 hours in a protective atmosphere; Preferably, the solution of the micro-mesoporous material precursor comprises a molecular sieve mother solution without a template; more preferably, the molecular sieve mother solution comprises seed crystals.
9. The air spring according to claim 1, wherein: The height of the embedded porous material is less than or equal to 30% of the height of the closed cavity; And / or, the volume of the embedded porous material is less than or equal to 30% of the volume of the closed cavity.
10. The air spring according to claim 1, wherein: The pressure of the gas filled in the closed cavity is 1 bar-10 bar; Preferably, the gas includes one or a combination of two or more of air, nitrogen, CO2, carbon tetrafluoride, helium, neon, and argon.
11. The air spring according to claim 1, wherein: The through hole in the piston includes a positive one-way hole and a negative one-way hole; a damping valve is respectively arranged in the positive one-way hole and the negative one-way hole; Preferably, the top aperture of the positive one-way hole is larger than the bottom aperture, and the top aperture of the negative one-way hole is smaller than the bottom aperture; More preferably, the ratio of the top aperture to the bottom aperture of the positive one-way hole is greater than 1:1 and less than or equal to 10:1; More preferably, the ratio of the top aperture diameter to the bottom aperture diameter of the negative unidirectional hole is greater than 1:1 and less than or equal to 10:
1.
12. The air spring according to claim 11, wherein: The top opening area of the positive one-way hole accounts for less than 10% of the top surface area of the piston, and the bottom opening area of the positive one-way hole accounts for less than 10% of the bottom surface area of the piston; And / or, the top opening area of the negative one-way hole accounts for less than 10% of the top surface area of the piston, and the bottom opening area of the negative one-way hole accounts for less than 10% of the bottom surface area of the piston; Preferably, there are more than two positive one-way holes and / or there are more than two negative one-way holes, and the positive one-way holes and the one-way holes are alternately distributed in the piston, the positive one-way holes are symmetrically distributed, and the negative one-way holes are evenly distributed.
13. A shock absorbing device comprising the air spring according to any one of claims 1 to 12; The shock absorbing equipment includes one or a combination of two or more of the following: bed frame gas pressure rods, door and window cabinet gas pressure rods, hood gas pressure rods, cab gas pressure rods, medical equipment gas pressure rods, office chair gas pressure rods, mountain bike front fork suspension and rear frame shock absorbers, car seat angle adjusters, and car suspension shock absorbers.
Citation Information
Cited By
Air spring and use thereof
WO2026108884A1